Entrepreneurship : Sunny Abadi CarWash / Noramiza Saji, Wan Nur Shafiqah Nadia W.M. and Malini Shukri - Saji, Noramiza; W.M. Shukri, Wan Nur Shafiqah Nadia; Shukri, Malini (2008)
Sunny Abadi Car Wash Sdn. Bhd. is a private limited company. Our company offer snow car wash services include exterior cleaning, interior cleaning, and engine cleaning for the customer. Our company equipped with all the necessary equipment and machine that will help the operation process run smoothly. The location of this business is at Lot 1314, Kampung Alor Pasir, 16800 Pasir Puteh, Kelantan. Our company total initial project cost is RM 37939. This include cash from shareholder is RM 21000 and we made from CIMB is RM 14349. We believe that this business will have wide market potential because nowadays people prefer to wash car at car wash centre than wash by self. We expected that our business will get attention from the customer and will encourage profit.